(untitled) (Nepal Journal of Epidemiology, 2018)
The burden of cancer is estimated to be increasing in Nepal, whilst the country lacks national established guidelines or protocols for referral of cancer cases. Cancer patients are presenting many different health facilities throughout the country. In rural areas almost all cancer patients have their first diagnosis when visiting a health assistant or nurse at their nearest primary health care delivery service. If cancer is suspected, health care assistants or nurses will refer the patient to a medical doctor at the primary health centre, or refer the patient directly to the cancer treatment centre or oncology department of the closest hospital. Patients from urban areas will usually be seen for the first time by a medical doctor initially and then referred to either the cancer treatment centre or oncology department of the hospital. Both in rural and urban areas the referral for treatment is determined by both the patients’ capacity to pay for treatment own healthcare, as well as their geographical location (i.e. availability and accessibility of cancer treatment services.